2012
DOI: 10.1016/j.intell.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Differential epidemiology: IQ, neuroticism, and chronic disease by the 50 U.S. states

Abstract: Current research shows that geo-political units (e.g., the 50 U.S. states) vary meaningfully on psychological dimensions like intelligence (IQ) and neuroticism (N). A new scientific discipline has also emerged, differential epidemiology, focused on how psychological variables affect health. We integrate these areas by reporting large correlations between aggregate-level IQ and N (measured for the 50 U.S. states) and state differences in rates of chronic disease (e.g., stroke, heart disease). Controlling for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…This relationship also has been found at the state level of analysis by Pesta, Bertsch, McDaniel, Mahoney, and Poznanski (2012), who reported that the Rentfrow et al (2008) state estimates of neuroticism were related to the state prevalence of heart disease. However, an individual-level prospective study by Nakaya et al (2005) did not find that neuroticism was a risk factor for heart disease.…”
supporting
confidence: 59%
“…This relationship also has been found at the state level of analysis by Pesta, Bertsch, McDaniel, Mahoney, and Poznanski (2012), who reported that the Rentfrow et al (2008) state estimates of neuroticism were related to the state prevalence of heart disease. However, an individual-level prospective study by Nakaya et al (2005) did not find that neuroticism was a risk factor for heart disease.…”
supporting
confidence: 59%
“…What explains the pattern of results we found? Pesta, Bertsch, McDaniel, Mahoney, and Poznanski (2012) speculate that founder effects may partly explain why states vary on psychological dimensions. Specifically, both social (e.g., religious beliefs and customs) and genetic (e.g., IQ and personality, in part) factors characterize the settlers of a particular geographic area.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of our findings, it is worthwhile to suggest that high IQ societies may have anticipated that it is not worthwhile for them to spend more on health insurance. A possible reason is that high IQ societies have less prevalence of diseases (e.g., HIV, heart disease, diabetes, obesity, stroke, and high blood pressure), and thus, they tend to have better health status and are less vulnerable to morbidity and mortality risk (Lynn & Vanhanen, 2012;Pesta, Bertsch, McDaniel, Mahoney, & Poznanski, 2012). This is in contrast to least-developed low-IQ societies with a proportionally higher probability of diseases and illnesses that raise the cost of insurance premiums (Chernew et al, 2003).…”
Section: Resultsmentioning
confidence: 99%